KUA's Efforts in Maintaining Harmonious Families in Families with Different Religions Based on the Value of Religious Moderation (Case Study of Manik Maraja Village, Sidamanik District) - Ardiansyah Nasution; Azwani Lubis (Dinasti Research, 2024)
The purpose of this paper is to find out the efforts of the Religious Affairs Office (KUA) in maintaining a harmonious family in families with different religions based on the value of religious moderation. Basically, the KUA is an institution under the auspices of the Ministry of Religious Affairs that directly interacts in the scope of the community area. Where when Manik Maraja Village was dubbed as the village of religious moderation, due to the plurality of its citizens, both religion and ethnic culture. This is where the role of the KUA is needed in maintaining a harmonious family in families with different religious backgrounds based on the value of religious moderation. In describing this study in detail, it is formulated How does the value of religious moderation affect maintaining a harmonious family in families of different religions? How are the efforts of the KUA in maintaining harmonious families in families of different religions based on the value of religious moderation? The purpose of this formulation is to know the value of religious moderation influences in maintaining harmonious families in families of different religions, and to know the efforts of the KUA in maintaining harmonious families in families of different religions based on the value of religious moderation. The method used by the author in this research is qualitative with an empirical approach. The conclusion of this research is that the KUA is a very important institution in maintaining harmonious families in families of different religions based on the value of religious moderation as evidenced by the holding of various counseling with constructive material as well as direct interaction by religious and community leaders at events in Manik Maraja Village. This aims to achieve the maintenance of a harmonious family in families with different religious backgrounds.